Unexplained tales: Cinderella and Prince Cinders - Canals Botines, Mireia; Raluy Alonso, Ángel (European Public & Social Innovation Review, 2025)
Introduction: Storytelling is an age-old human practice, and contemporary children's literature has attempted to reverse old clichés by including alternative characters. However, studies indicate that children, even as young as 4 or 5 years old, show discomfort with gender role reversal. Methodology: This article critically analyses gender roles in children's literature through a comparative textual study between the classic version of Cinderella and its reinterpretation in Prince Cinders. The language and literary devices used in both versions are examined. Results: The analysis reveals a significant evolution in the treatment of the characters, aimed at promoting more inclusive and plural educational models. Discussion: The dominant presence of non-traditional roles in the new narratives is key to positively influencing children's perceptions of gender, although children's initial bewilderment is evidence of the persistence of socially entrenched stereotypes. Conclusions: Children's literature can be a transformative tool for challenging and redefining gender norms, and reinterpretations such as Prince Cinders are an important step towards a more egalitarian education from the earliest ages.